Análisis de la planificación estratégica del sector eléctrico ecuatoriano – segmento generación - y su relación sobre la vulnerabilidad y dependencia eléctrica del Ecuador para el periodo 2010-2015 - Orejuela Puente, Aleida Patricia (2013)
The present investigation focuses on the analysis of the strategic planning in the Ecuadorian electricity sector and the relation with the dependence and vulnerability of the country`s electricity. In the first instance we analyze the condition of the art of the theories and the conceptual models of the strategic planning, in order to know which is the thought of the principal modern authors related to this topic, and also, for business administration, is of great importance for the organizations, public or private, and especially for the development of the strategic sectors of a country like ours. The second part of the research approaches the problematic of the Ecuadorian electricity sector, the beginning, the current situation, and the main technical characteristics as maximum annual energy demand, electricity matrix composition, and organizational structure of the entities of this sector. Also we present which policies are defined by the Ecuadorian government, as part of the National Plan for Good Living 2009-2013, to meet the strategic objectives for the development and growth of this sector in the medium and long term, and thus, ensure, firstly organized growth for the Ecuadorian generation and, on appeal, the energy supply to all productive sectors of the country with quality and safety criteria; thus contributing to the proposed change the productive matrix of the country. Finally, establishing the criteria for assessing the degree of success of strategic planning in the electrical power sector implemented Ecuador for the period 2010 - 2015, and also discusses the relationship between strategic planning and vulnerability and dependence of Ecuadorian electrical power system. The keywords of this research are:  Planning  Strategy  Electrical Power System  Electrical Matrix  Dependency  Vulnerability